DESIGN AND IMPLIMENTATION OF A LOW COST HEARING AID DEVICE (FUDMA JOURNAL OF SCIENCES, 2023)
Loss of hearing power might be due to several reasons such as; old age, hearing loud sound that can damage the auditory system and so on. Hearing aid device is an elecronic system used to enhance weak sound signals to a level that those with different levels of partial hearing loss can hear. This paper considers the design and implimentation of a low cost hearing aid device.Design equations were employed to calculate the physical parameters of the different units of the circuit. The frequency response test showed a constant flat response from to about 2 at gain of the maximum current drawn by the device is per second. When tested on 4 people with partial hearing problem, the results showed that there was a significant improvement in the hearing ability of all the patients tested. The paper recommends that design of digital hearing aid be considered to enhance output signal quality and feedback control.
Keywords: Hearing aid. Hearing loss, Transducer, Frequency response and Amplifier